A new form of beet cossettes – the way to get and benefits - Lulka, Alexander; Mironchuk, Valeriy; Adamenko, Andriy (My University, 2013)
The capacity and stability of beet sugar plant’s functioning depends mostly on the work of diffuse device which is sensible to the beet cossettes’ quality. We get cossettes from beet slicers reducing suger beets by diffuser knives. That’s why knives’ form, type and derived cossettes play an important role in sugur production.
Keywords: бурякова стружка; бурякорізальні ножі; дифузія; нарізання; свеклорезные ножи; резка; beet cossettes; beet cutting knives; diffusion; cutting; кафедра готельно-ресторанної справи; кафедра технологічного обладнання та комп’ютерних технологій проектування